Positive and Negative Affect Schedule-Short Form: Factorial Invariance and Optimistic and Pessimistic Affective Profiles in Spanish Children - Sanmartín, Ricardo; Vicent, María; Gonzálvez, Carolina; Inglés, Cándido J.; Díaz-Herrero, Ángela; Granados, Lucía; García-Fernández, José M. (Frontiers in Psychology, 2018)
The distinction in recent years between positive affect (PA) and negative affect (NA) is becoming increasingly important due to their relationship with depression and anxiety. This work is composed of two studies. The first study aimed to validate the brief version of the Positive and Negative Affect Schedule for Children-Short Form (PANAS-C-SF) in a Spanish child sample. The second study sought to check the existence of four affective profiles: self-fulfilling (high PA and low NA), low affective (low PA and NA), high affective (high PA and NA), and self-destructive (low PA and high NA) and to relate them to optimism and pessimism. Samples for both studies were composed of 647 and 1,296 Spanish students (between 8 and 11 years), respectively. Through various multigroup confirmatory factor analyses (MCA), the invariance of the PANAS-SF and the lack of significant gender differences in the latent means were verified. In addition, cluster analysis confirmed the existence of the appropriate profiles. In this case, the self-fulfilling profile correlated with high scores in optimism and low scores pessimism, whereas the self-destructive profile correlated in the opposite direction. These contributions represent an advance in the study of child affect.